Rhythm measures with language-independent segmentation - Loukina, A; Kochanski, G; Shih, C; Keane, E; Watson, I (International Speech Communication Association, 2009)
We compare 15 measures of speech rhythm based on an automatic segmentation of speech into vowel-like and consonant-like regions. This allows us to apply identical segmentation criteria to all languages and to compute rhythm measures over a large corpus. It may also approximate more closely the segmentation available to pre-lexical infants, who apparently can discriminate between languages. We find that within-language variation is large and comparable to the between-languages differences we observed. We evaluate the success of different measures in separating languages and show that the efficiency of measures depends on the languages included in the corpus. Rhythm appears to be described by two dimensions and different published rhythm measures capture different aspects of it.